Lethal CD4 T Cell Responses Induced by Vaccination Against Staphylococcus aureus Bacteremia. (21st February 2017) - Karauzum, Hatice; Haudenschild, Christian C.; Moore, Ian N.; Mahmoudieh, Mahta; Barber, Daniel L.; Datta, Sandip K.
Abstract: Multiple candidate vaccines against Staphylococcus aureus infections have failed in clinical trials. Analysis of a recent prematurely halted vaccine trial revealed increased mortality rates among vaccine recipients in whom postsurgical S. aureus infection developed, emphasizing the potential for induction of detrimental immune responses and the need to better understand the requirements for protective immunity against S. aureus . These failures of single-antigen vaccines have prompted ongoing development of multicomponent vaccines to target the multitude of S. aureus virulence factors. In the current study, we used lethally irradiated S. aureus as a model multicomponent vaccine and showed that vaccination of mice decreased survival in a bacteremia challenge model. These deleterious effects were due to a CD4 T-cell–dependent interferon γ response and could be prevented by inhibiting development of this response during vaccination. Our results identify the potential for vaccination to induce pathological immune responses, and they have implications for recent vaccine failures and the design of future staphylococcal vaccines.